The crises of civilization :exploring global and planetary histories - Dipesh Chakrabarty (OUP, 2018)
Societies that have long wrestled with the legacies of colonialism now confront both a crisis of globalization and a crisis of climate. This collection of essays by a leading scholar of postcolonial studies and environmental humanities examines these distinct - but interrelated - crises side by side. The first series of essays, 'Global Worlds', details how varied ideas of civilization and humanism have shaped ideas about a global humanity in the lingering twilight of the European empires - and outlines the conflicts and connections that arise from global encounters in our postcolonial age. The essays of 'The Planetary Human' explore the significance of planetary climate change for humanistic and postcolonial thought. The crisis of climate change demands not only critiques of capitalism and inequality, but also new thinking about the human species as a whole ― and about our patterns of justice, our writing of history, and our relationship with nature in the age of the Anthropocene.